1980
DOI: 10.3358/shokueishi.21.177
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Disappearance Rate and Residual Levels of Monensin in Chick Tissues by Quantitative Thin-layer Bioautography

Abstract: The procedures (purification, developing solvent, medium) used in the original thinlayer bioautographic method of Donoho and Kline for the determination of monensin in chick tissues were modified to improve the recovery and sensitivity of the assay. Recoveries of monensin from fortified tissue samples were 92.9% from fat, 86.0% from liver and 104.4% from muscle. The assay sensitivity was improved to give a detection limit of 0.01ppm in fat and 0.0125ppm in other tissues. Feed containing monensin at 80, 100 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Donoho found Mo-Na residues between 0.046 and 0.116, whereas 0.01 mg kg -1 were found in study 2. Thus Donoho values were in the same ranges as earlier findings of Donoho and Kline (1968) for eight weeks old chickens and Okada et al (1980) on nine weeks old chickens. Thus, direct comparison of data on Mo-Na residues is difficult as lipid content in the carcass of broilers increases with increasing of bodyweight and fat content of the skin/fat samples may vary accordingly.…”
Section: Introductionsupporting
confidence: 89%
“…Donoho found Mo-Na residues between 0.046 and 0.116, whereas 0.01 mg kg -1 were found in study 2. Thus Donoho values were in the same ranges as earlier findings of Donoho and Kline (1968) for eight weeks old chickens and Okada et al (1980) on nine weeks old chickens. Thus, direct comparison of data on Mo-Na residues is difficult as lipid content in the carcass of broilers increases with increasing of bodyweight and fat content of the skin/fat samples may vary accordingly.…”
Section: Introductionsupporting
confidence: 89%
“…Using bioautographic assays, Donoho & Kline (1968) found that at zero time withdrawal from medicated feed, poultry fat contained approximately 0.1 /ig/kg monen-sin while other edible tissues contained no detectable residue when assayed at a detection limit of 0.025 to 0.05 //g/kg. In a study by Okada et al (1980), there was a trace of monensin in fat, liver, kidney and muscle at zero time withdrawal (detection limit 0.01 /zg/kg). A sodium partitioning assay for monensin has produced conflicting data for monensin residues after recommended doses (110 /ig/kg feed).…”
Section: Tissue Concentrationsmentioning
confidence: 99%
“…Residue studies in the literature Two published studies have been carried out in the chicken to determine monensin residues in tissues in practical conditions of use. In the first study (Okada, 1980) four groups of 5 male chickens were administered 120 mg monensin sodium kg -1 feed for life time, then slaughtered after 0, 1, 2 and 3 days withdrawal of the supplemented feed. Using a quantitative thin layer chromatography with a limit of quantification of 0.01 and 0.0125 mg monensin kg -1 for the fat and the other tissues (liver, kidneys and muscle) respectively, it has been shown that the highest concentrations were measured in the fat then the liver, that no monensin was detectable in tissues except fat after a 1-day withdrawal period and in any tissue after 2 days.…”
Section: 61mentioning
confidence: 99%